Binding three-particles at the edge of stability - Frederico, T.; Delfino, A.; Tomio, L. (Springer, 2002)
The stability threshold for an Efimov state is determined as a function of the physical scales of the system. Light exotic nuclei and triatomic molecules are investigated. Scaling, universality, and renormalization-group invariance properties are discussed in this context.